Michael Vey : the prisoner of cell 25 / 1. - Evans, Richard Paul (Michael Vey, 2011)
Fourteen-year-old Michael discovers he has special electrical powers and, with the help of his best friends, becomes aware that there are other teens with similar powers, but something or someone is hunting them and, after Michael's mother is kidnapped, he will need to rely on his powers and his friends to rescue his mom, protect himself, and save the others.